2007
DOI: 10.1002/bip.20866
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into cold inactivation of tryptophanase and cold adaptation of subtilisin S41

Abstract: A wide variety of enzymes can undergo a reversible loss of activity at low temperature, a process that is termed cold inactivation. This phenomenon is found in oligomeric enzymes such as tryptophanase (Trpase) and other pyridoxal phosphate dependent enzymes. On the other hand, cold‐adapted, or psychrophilic enzymes, isolated from organisms able to thrive in permanently cold environments, have optimal activity at low temperature, which is associated with low thermal stability. Since cold inactivation may be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…The apparently lower stability at 0°C could be a consequence of cold inactivation. This phenomenon which has been observed with several oligomeric enzymes is assumed to be a consequence of weakened hydrophobic interactions at subunit interfaces (Almog et al, 2007; Erez et al, 2002; Ishikura et al, 2003). RADH shows highest stability at 15°C (half‐life: 138 h, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The apparently lower stability at 0°C could be a consequence of cold inactivation. This phenomenon which has been observed with several oligomeric enzymes is assumed to be a consequence of weakened hydrophobic interactions at subunit interfaces (Almog et al, 2007; Erez et al, 2002; Ishikura et al, 2003). RADH shows highest stability at 15°C (half‐life: 138 h, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, it requires certain monovalent cations (K þ , NH þ 4 , TI þ ) for activity and for tight PLP binding [4 -6]. The enzyme undergoes a reversible inactivation followed by dissociation into dimers or monomers, depending on the bacteria species, after incubation for several hours at 28C [7]. The enzymatic reaction with tryptophan is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that optimization of the catalytic properties is achieved through increased local or global molecular flexibility, facilitating the conformational changes required for catalytic function at low temperatures [60À63]. None of these structural features is present in all cold adapted enzymes, however, and results show that each protein family adopts its own strategies in coping with temperature adaptation [3,13,63,66]. Decreased structural stability in comparison to related homologous enzymes from meso-and thermophilic organisms is indeed a characteristic feature of cold adapted enzymes [60,63À65].…”
Section: Distinguishing Featuresmentioning
confidence: 99%
“…Decreased structural stability in comparison to related homologous enzymes from meso-and thermophilic organisms is indeed a characteristic feature of cold adapted enzymes [60,63À65]. Based on structural analysis, a common feature of the cold adapted subtilases is the anionic character of their molecular surfaces, arising from uncompensated negative charges of Asp and Glu residues [10,13,14,66]. Several comparative studies of metagenomic and genomic data from psychrophilic organisms have been in agreement with these results, but have also indicated that cold enzymes contain relatively high levels of polar uncharged amino acid residues and significant trends for amino acid substitutions leading to higher structural flexibility (for review see: Casanueva et al [3]).…”
Section: Distinguishing Featuresmentioning
confidence: 99%
See 1 more Smart Citation